FAKTOR KONDISI LINGKUNGAN SERTA KARAKTERISTIK DAN KAPABILITAS INSTANSI PELAKSANA TERHADAP PELAKSANAAN TRIAS UKS DALAM PENERAPAN SEKOLAH SEHAT TINGKAT SD/MI DI WILAYAH KERJA PUSKESMAS KEDUNGMUNDU - Tika Purbadiyanti Pranata; Sutopo Patria Jati; Eka Yunila Fatmasari (Jurnal Kesehatan Masyarakat (Undip), 2020)
Problems regarding bad hygiene and healthy behavior (PHBS) are still common in elementary school age children. The results of health screening at primary schools in the Kedungmundu’s Community Health Center in 2018 indicate that there are still students who have poor nutritional status and are at risk of developing anemia. In addition, there was a decrease in level in 2018 to 28 UKS minimum level and 2 UKS standard level. This study aims to determine the factors associated with UKS level in the application of healthy schools at the elementary school level. This research is a quantitative study with a research design using cross sectional study. Samples were taken by means of a total population of 29 elementary schools. The results showed that the related variables were environmental conditions (p = 0,008), characteristics and capabilities of implementing agencies (p = 0,001). While the unrelated variable is the relationship between organizations (p = 0,061), organizational resources 0,272). From these results schools should be expected to form a UKS implementation team, increase the number of small doctors, complete the UKS facilities, make collaboration with relevant parties, and hold regular meetings held by the UKS implementation team.